Solve for $x$ and $n$ in the equation $$ \dfrac{x^2 + 7x +1}{ x^2 + x +1}= 3n,\qquad n \in \Bbb{Z}.$$ The original problem was a trigonometric equation but solved it till I got stuck here. I am a high school student who is self studying and preparing for college entrance exam. Original problem was a trigonometric equation which came from 'cengage exam crack'.

[After Mark's and Jyrki's hints in the comments, I got the answer and posted it below.] Original problem: enter image description here

  • $\begingroup$ Is the value of $n$ known, or also for you to figure out? $\endgroup$ – Jyrki Lahtonen Apr 12 at 3:33
  • 1
    $\begingroup$ Have you tried clearing fractions and using the quadratic formula? You need the bit under the square root to be positive. @JyrkiLahtonen's comment gives you the possible values of $n$ $\endgroup$ – Mark Bennet Apr 12 at 3:44
  • 2
    $\begingroup$ @MarkBennet thank you. I got the answer. I also posted in below. $\endgroup$ – user541396 Apr 12 at 4:07
  • 2
    $\begingroup$ While I have nominated this question for reopening, I would personally like to seem more context included in the question. Specifically, you say that the problem started life as a trigonometric equation. Editing this original trigonometric equation into the question would help pin down questions of domain (i.e. what values of $x$ and $n$ actually make sense, given that they have to be fed to some trig function). A more complete reference to "engage exam crack" (whatever that is) would also be helpful. $\endgroup$ – Xander Henderson Apr 15 at 16:41
  • 1
    $\begingroup$ @XanderHenderson what do you mean by 'more complete reference'? $\endgroup$ – user541396 Apr 17 at 13:42

1) Convert the problem into quadratic $ x^2(1-3n) + x(7-3n) + 1-3n = 0 $

2) set discriminant greater than equal to $0$

3) find the range of $n $

4) find the possible values of n which are $(0,1,-1)$

5) plug them back in to find values of $x$

  • $\begingroup$ That's a nice way of combining the steps. Well done! $\endgroup$ – Jyrki Lahtonen Apr 12 at 6:40

$3n =\dfrac{x^2 + 7x +1}{ x^2 + x +1} $ so $3nx^2+3nx+3n =x^2+7x+1 $ so $(3n-1)x^2+(3n-7)x+3n-1 =0 $ or

$\begin{array}\\ x &=\dfrac{-3n+7\pm \sqrt{(3n-7)^2-4(3n-1)^2}}{2(3n-1)}\\ &=\dfrac{-3n+7\pm \sqrt{(3n-7-2(3n-1))(3n-7+2(3n-1))}}{2(3n-1)}\\ &=\dfrac{-3n+7\pm \sqrt{(-3n-5)(9n-9)}}{2(3n-1)}\\ &=\dfrac{-3n+7\pm 3\sqrt{(-3n-5)(n-1)}}{2(3n-1)}\\ \end{array} $

If nothing is specified about $x$, this is as far as we can go.

If $x$ has to be real, then $(3n+5)(n-1) \le 0$ so that $-\dfrac53 \le n \le 1$. Since $n$ is an integer, $n = -1, 0, 1$.

If $x$ is supposed to be rational, then $(3n-7)^2-4(3n-1)^2 =m^2 $. From the preceding result, $n=1 \implies m^2 =4^2-4(2)^2 =0 $, $n=0 \implies m^2 =7^2-4(1)^2 =45 $, $n=-1 \implies m^2 =10^2-4(-4)^2 =36 $.

Therefore the only rational solutions with integer $n$ are $n=1, 0, -1$ for which $n=1 \implies x =\dfrac{-3n+7\pm 3\sqrt{(-3n-5)(n-1)}}{2(3n-1)} =\dfrac{4}{4} =1 $, $n=0 \implies x =\dfrac{-3n+7\pm 3\sqrt{(-3n-5)(n-1)}}{2(3n-1)} =\dfrac{7\pm 3\sqrt{5}}{-2} $, and $n=-1 \implies x =\dfrac{-3n+7\pm 3\sqrt{(-3n-5)(n-1)}}{2(3n-1)} =\dfrac{-10\pm 4}{-8} =\dfrac{-14, -6}{-8} =\dfrac74, \dfrac52 $.

  • 1
    $\begingroup$ Why did you exclude n= 0, if it is because it doesn't provide a rational solution , then question doesn't say anything about X to be rational or irrational but only real. $\endgroup$ – user541396 Apr 12 at 5:16
  • $\begingroup$ You are right. Added that case and upvoted your comment. Thanks, $\endgroup$ – marty cohen Apr 12 at 5:26
  • $\begingroup$ The question doesn't actually say anything about $x$ being real, so why is everyone making that assumption? $\endgroup$ – Gerry Myerson Apr 15 at 5:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.